Integrating ISO 9001:2015 Gap Analysis and the Balanced Scorecard for Sustainable Profitability: A Case Study of Radja Gurame Cempaka Putih Restaurant - Tangie, Maria Lita; Imaroh, Tukhas Shilul (Dinasti International Journal of Digital Business Management, 2026)
This research examines the causes of financial performance declining and of low customer review ratings at the Radja Gurame Cempaka Putih outlet of PT Selera Radja Sejahtera, which poses a threat to business sustainability, and aims to restore its profitability by identifying gaps in the quality management system and organizational performance. A qualitative descriptive method was applied through management interviews, focus group discussions with key employees, customer interviews, field observations, and analysis of secondary data. The analysis integrates gap analysis of the ISO 9001:2015 quality management system, Balanced Scorecard performance perspectives, Cause and Effect analysis, and Resourced-Based View evaluation. The results reveal seven key findings: significant gap exists between operational practices and the formal quality management system, data-driven performance measurement and decision-making systems are not yet established, product and service quality inconsistencies occur under high operational load, product and service quality constitute key intangible resource-based strengths, human resource management is not yet system-based, technology utilization remains operational rather than strategic, and internal resource advantages have not been converted into sustainable financial performance. The study proposes a Balanced Scorecard-based strategy map to restore a sustainable profitability over a three-year horizon.